Eficácia e efeitos hemodinâmicos da anestesia raquidiana com ropivacaína isobárica, hipobárica ou hiperbárica seletiva em cães anestesiados com isofluorano - Abimussi, Caio José Xavier [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objetivou-se avaliar a anestesia raquidiana com ropivacaína em cães alterando a baricidade do anestésico local, investigando as alterações hemodinâmicas e complicações. Foram utilizados seis cães, Beagle, 4 anos, submetidos a anestesia inalatória com isofluorano e aos tratamentos: Ghipo = anestesia raquidiana hipobárica (0,5 mL NaCl 0,9% + 0,5 mL ropivacaína 0,75%); Giso = anestesia raquidiana isobárica (0,5 mL NaCl 1,53% + 0,5 mL ropivacaína 0,75%); Ghiper = anestesia raquidiana hiperbárica (0,5 mL glicose 10% + 0,5 mL ropivacaína 0,75%). Após indução anestésica e manutenção com isofluorano, os animais foram posicionados em decúbito lateral direito para a passagem de um cateter de artéria pulmonar pela veia jugular esquerda. Após esse procedimento, a punção subaracnóide foi realizada entre L5-L6 com uma agulha espinhal 22G, seguida da administração de 1 mL de anestésico local em 1 min. Os animais foram mantidos por 60 minutos anestesiados em decúbito ventral. A FC, f, PAM, DC, PAPm e TºC apresentaram aumento progressivo em todos os grupos enquanto que a PCPm, apenas no GHIPO, aumentou ao longo de todos os momentos. O IRPT no GISO apresentou valores significativamente superiores no M1, M5 e M10 comparado aos demais grupos, exceto no M5, em que o GISO diferiu somente do GHIPER. O IRVP no GISO aumentou no M5 em comparação ao MB. Foram observados efeitos adversos como déficit motor unilateral, atonia vesical, excitação, dor aguda e quemose. Conclui-se que as alterações hemodinâmicas não foram relevantes, embora a anestesia inalatória com isofluorano tenha influído sobre os resultados obtidos.

The aim of the study was to assess spinal anesthesia with ropivacaine in dogs altering the local anesthetic agent’s baricity in order to investigate hemodynamic changes and complications. Six beagle dogs aged 4 years old were anesthetized with isoflurane and subjected to the treatments: Ghypo = spinal anesthesia with hypobaric ropivacaine (0.5 mL of 0.9% NaCl + 0.5 mL ropivacaine at 0,75%); Giso = isobaric spinal anesthesia (0.5 mL of 0,906% NaCl + 0.5 mL ropivacaine at 0,75%); Ghyper = hyperbaric spinal anesthesia (0.5 mL of 10% glucose + 0.5 mL ropivacaine at 0.75%). After induction to anesthesia and maintenance with isoflurane, animals were positioned in right lateral recumbency for pulmonary artery catheterization through the left jugular vein. Rightafter, spinal anesthesia was performed between L5-L6 using a 22G Quincke tip needle, followed by administration of 1 mL of local anesthetic during 1 minute. Animals were maintained under anesthesia for 60 minutes in ventral recumbency. HR, FR, MAP, CO, mPAP and body temperature progressively increased in all groups. whereas PCWP increased only in GHYPO at all time points. The TPRI showed significantly higher values in GISO at M1, M5 and M10 compared to the other groups, except for M5, during which GISO differed only from GHYPER. The PVRI increased at M5 compared to MB in GISO. Side effects such as unilateral motor deficit, bladder atony, excitation, acute pain and chemosis were observed. In conclusion, the hemodynamic changes were not relevant, although inhalation anesthesia with isoflurane might have influenced the results.
Efficacy and hemodynamic effects of spinal anesthesia with isobaric, hypobaric or hyperbaric ropivacaine in dogs anesthetized with isoflurane
Keywords: Anestesia local; Anestesia balanceada; Raquianestesia; Medula espinhal; Animais domésticos; Spinal anesthesia; Local anesthetics; Balanced anesthesia; Spinal cord; Domestic animals